Nutrigenomics and its Role in Periodontal Health – A Review - Shyam Sundar Behura1 , E.Rajesh2 , Abinash Patra3 , N.Aravindha Babu4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Nutrigenomics is an emerging form of science involving tools that assess the benefit of diet and nutritionin various disease conditions at molecular and genetic level. Nutrigenomics investigates the relationship ofnutrient regimen in maintaining health. This article reviews the role of nutrients in maintaining periodontalhealth and the use of nutrigenomics in understanding genotype, phenotype diet interactions on periodontalhealth of an individual and the effect of dietary modification on periodontal disease progression.